GENDER MAINSTREAMING, ACCOUNTABILITY AND SOCIAL WELFARE A CASE OF OXFAM, SOUTH SUDAN - Dr. Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
This study examined the relationship between Gender mainstreaming, Accountability and Social welfare in South Sudan. The objectives of the study were; examine the relationship between Gender mainstreaming and Social welfare, evaluate the relationship between Accountability and Social welfare and to study the factor structure of Gender mainstreaming and Accountability on Social welfare. The study design was descriptive and a case study while using qualitative and quantitative approaches. The study population was 466, the sampling technique was purposive and simple random and the sample size determination was made using Krejcie and Morgan (1970). The sample size was 180. Data was analyzed using Statistical package for social scientists (SPSS 20.0). The major findings of the study were that, there is a significant positive correlation between; between Gender mainstreaming and Social welfare (r = 0.307, P-value < 0.01); Accountability and Social welfare (r = 0.200, P-value < 0.01) and R= 0.603) a combination of Gender mainstreaming andAccountabilityin assessing the level to which they can predict the level of Social welfare. These variables explained 43.7% of the variance of Social welfare (R Square =.437). The most influential predictor of Social welfare was Gender mainstreaming (β = .532, Sig. 242). Accountability is less likely to influence Social welfare since it portrays low significance (β = .414, Sig. 373) in the model The study recommended that the organisations should identify the factors that create and increase gender biases within its atmosphere such as the vision and objectives, structure and policy, practices, programs and services, beliefs and attitudes as well as the practices of the staff members, A sense of responsibility should be instilled in all staff and service providers in OXFAM GB as it will increase worker output quality and eventually improve service delivery and that the organization should eliminate any biases in the hiring, firing and promotion of male and female staff.